Cover Feature: Synthesis of Pyrrolo[2, 1‐a]isoquinoline Class of Natural Product Crispine A (Eur. J. Org. Chem. 35/2021). Issue 35 (13th September 2021) - Mohan, Chithra; Krishna, R. Bharath; Sivanandan, Sudheesh T.; Ibnusaud, Ibrahim
Abstract : The Cover Feature shows naturally occurring (2 S, 3 S )‐ and (2 S, 3 R )‐tetrahydro‐3‐hydroxy‐5‐oxo‐2, 3‐furan dicarboxylic acid bearing, chemically amenable functional groups that are an ideal choice for the enantiopure synthesis of the (−)‐ and (+)‐Crispine A, respectively. The diastereomeric natural products are conveniently converted to desirable enantiomers of Crispine A through the chiral pool strategy. This exciting and efficient strategy is one of the well‐explored trends in synthetic organic chemistry, especially regarding molecules procured from tropical plant material (Nature) and serves as key step in the enantiopure synthesis of small‐molecule natural products. More information can be found in the Minireview by C. Mohan, I. Ibnusaud et al .